ANALISIS MISKONSEPSI SISWA PADA OPERASI PENJUMLAHAN DAN PENGURANGAN PECAHAN DI KELAS V SEKOLAH DASAR - Viviana, Viviana; Bistari, Bistari; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to study and describe the forms of misconceptions and causes of misconceptions that occured in class 5th grade students of Sekolah Dasar Negeri 24 Pontianak. The method used in this research is descriptive method with a case study research form. The subjects of this study were 13 students of 5th A of Sekolah Dasar Negeri 24 Pontianak, who determined based on the students answers on the essay test with CRI. The research instrument used in this study consisted of an essay test submitted by CRI and interview guidelines. The results of research on 13 students who oppose misconceptions, there are 3 forms of misconceptions experienced by students, consisting of overgeneralizing, misconceptions consisting of students who answer fraction addition questions by summing numerators with numerators and denominators with denominators, the overspecializing, which can be considered a summing question by using fractions multiplication, and systematic misconceptions Â which can be considered astudents work on problems with the pattern of answers to repeated misconceptions. Based on the results of the interview, the causes of students' misconceptions about themselves, lack of explanation on learning mathematics, incomplete reasons, lack of arithmetic skills, and from an environment consisting of non-conducive classes, ways of teaching teachers, monotonous learning methods, and learning media that are less interesting.Â Keywords: Analysis, Misconception, Operation of Addition and Subtraction of Fractions